2020
DOI: 10.1016/j.corsci.2020.108594
|View full text |Cite
|
Sign up to set email alerts
|

Pitting corrosion of 17-4PH stainless steel manufactured by laser beam melting

Abstract: The pitting corrosion behaviour of a 17-4PH martensitic stainless steel (MSS) manufactured by power bed laser beam melting (LBM) was compared to that of a wrought MSS. More noble pitting potentials were measured for LBM samples, probably due to a smaller size of NbCs as compared to wrought MSS. The metastable pits were less numerous, but had a higher nucleation rate and longer life time for the LBM samples compared to the wrought MSS. This was explained by assuming a decrease in the repassivation ability of LB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 48 publications
10
39
0
Order By: Relevance
“…We showed, in a previous study on the corrosion behaviour of 17-4PH MSS manufactured by LBM, significant differences in the pitting susceptibility between LBM and conventional samples in NaCI solution [44]. A more positive pitting potential value was observed for the 17-4PH LBM MSS; this was attributed, at least partially, to smaller NbC precipitates, which acted as preferential pit initiation sites, in agreement with Clark et al [ 45].…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…We showed, in a previous study on the corrosion behaviour of 17-4PH MSS manufactured by LBM, significant differences in the pitting susceptibility between LBM and conventional samples in NaCI solution [44]. A more positive pitting potential value was observed for the 17-4PH LBM MSS; this was attributed, at least partially, to smaller NbC precipitates, which acted as preferential pit initiation sites, in agreement with Clark et al [ 45].…”
Section: Introductionsupporting
confidence: 89%
“…The differences in Cr content for the passive films formed on LBM and conventional MSSs could be explained by referring to the austenite content of the samples. Indeed, we showed in a previous study [ 44] that the austenite content was between 8 and 12 % and only 0.8 % for the LBM and conventional samples, respectively. Langberg et al [53] recently showed, for a super duplex stainless steel, that the passive film formed on ferrite had a higher Cr content than this one formed on austenite due to the higher Cr content in ferrite.…”
mentioning
confidence: 80%
See 3 more Smart Citations